Probing the microscopic environment of ²³Na ions in brain tissue by MRI: on the accuracy of different sampling schemes for the determination of rapid, biexponential decay at low signal-to-noise ratio - Lommen, Jonathan Manuel; Flassbeck, Sebastian; Behl, Nicolas G. R.; Niesporek, Sebastian; Bachert, Peter; Ladd, Mark E.; Nagel, Armin Michael (Magnetic resonance in medicine, 2018)
Purpose To investigate and to reduce influences on the determination of the short and long apparent transverse relaxation times ( , ) of 23Na in vivo with respect to signal sampling. Methods The accuracy of determination was analyzed in simulations for five different sampling schemes. The influence of noise in the parameter fit was investigated for three different models. A dedicated sampling scheme was developed for brain parenchyma by numerically optimizing the parameter estimation. This scheme was compared in vivo to linear sampling at 7T. Results For the considered sampling schemes, / exhibit an average bias of 3% / 4% with a variation of 25% / 15% based on simulations with previously published values. The accuracy could be improved with the optimized sampling scheme by strongly averaging the earliest sample. A fitting model with constant noise floor can increase accuracy while additional fitting of a noise term is only beneficial in case of sampling until late echo time > 80 ms. values in white matter were determined to be = 5.1 ± 0.8 / 4.2 ± 0.4 ms and = 35.7 ± 2.4 / 34.4 ± 1.5 ms using linear/optimized sampling. Conclusion Voxel-wise determination of 23Na is feasible in vivo. However, sampling and fitting methods have to be chosen carefully to retrieve accurate results. Magn Reson Med 80:571-584, 2018. © 2018 International Society for Magnetic Resonance in Medicine.
Gesehen am 02.03.2020